The Use of Interactive Powerpoint Media in Improving Student Learning Outcomes of MI Muhammadiyah Poso on Prayer Material - Irmayanti Bauda; Muhammad Sofian Hadi (English Language in Focus (ELIF), 2023)
AbstrakMedia adalah sebagai alat bantu dalam proses belajar mengajar. Keadaan siswa yang pada umumnya diajar dengan model pembelajaran secara langsung khususnya dengan menggunakan metode ceramah, menunjukkan bahwa siswa kurang bersemangat dalam menerima pelajaran, sehingga mengakibatkan pencapaian hasil belajar siswa yang kurang dari standar KKM. Penelitian ini bertujuan untuk mengetahui perbedaan peningkatan hasil belajar siswa MI. Muhammadiyah Poso dalam pembelajaran. Metode yang digunakan dalam penelitian ini adalah kualitatif. Populasi penelitian ini adalah siswa kelas III a dan kelas III b dengan sampel masing-masing kelas berjumlah 15 orang. Teknik  pengumpulan data yang digunakan yaitu teknik observasi dan tes. Hasil penelitian yang didapat adalah 1) terdapat peningkatan hasil belajar pada kelas IIIa dan IIIb, 2) terdapat peningkatan minat dan pemahaman selama proses pembelajaran berlangsung, dan 3) Terdapat perbedaan hasil belajar sebelum menggunakan media dengan sesudah menggunakan media. Disimpulkan dengan adanya media yang digunakan dalam pembelajaran, maka hasil belajar siswa pun mengalami peningkatan. Kata Kunci: Media, PowerPoint, hasil belajar, Sholat. AbstractMedia is a tool in the teaching and learning process. The condition of students who are generally taught by direct learning models, especially by using the lecture method, shows that students are less enthusiastic about receiving lessons, resulting in achievement of student learning outcomes that are less than the KKM standard. This study aims to determine differences in the improvement of MI students' learning outcomes. Muhammadiyah Poso in learning. The method used in this research is qualitative. The population of this study were students of class III a and class III b with a sample of 15 people from each class. Data collection techniques used are observation and test techniques. The research results obtained were 1) there was an increase in learning outcomes in class IIIa and IIIb, 2) there was an increase in interest and understanding during the learning process, and 3) there were differences in learning outcomes before using the media and after using the media. It was concluded that with the media used in learning, student learning outcomes also increased. Keywords: Media, PowerPoint, learning outcomes, Prayers.